PROGRAM PENGURANGAN PENGGUNAAN KANTONG PLASTIK DI PASAR PUCANG ANOM KOTA SURABAYA DALAM PANDANGAN TEORI IMPLEMENTASI KEBIJAKAN - Salsabila Mawardani; Lukman Arif (Journal Publicuho, 2023)
This study aims to find out the program to reduce the use of plastic bags at the Pucang Anom Market in Surabaya City in the View of Policy Implementation Theory. The research used qualitative research methods with a focus on the implementation of policies to reduce the use of plastic bags in traditional markets in Surabaya, according to George C. Edward III. The type of data in this research is through primary data sources and secondary data sources. Data collection techniques through observation, interviews, and documentation. The data analysis method used in this study is that of Miles and Huberman (2014: 8). Based on the results of observations at the Pucang Anom Market locus, there were still problems with shopping bags that were not environmentally friendly. This happened because the communication between the Surabaya City Environment Service and the Pucang Anom market management officer had not run optimally. well implemented bureaucratic structure, main tasks and functions have been running optimally in accordance with the provisions, the SOP has been running well according to the rules even though it is still not timely in imposing sanctions. With this in mind, a suggestion was formulated regarding the implementation of the policy for the Surabaya City Environment Service, which is expected to carry out socialization on an ongoing basis and provide sanctions for traders who violate it to provide a deterrent effect, and pay more attention to the stipulated time provisions